2000
DOI: 10.1054/bjoc.1999.1043
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C in human renal cell carcinomas: role in invasion and differential isoenzyme expression

Abstract: The role of protein kinase C (PKC) in in vitro invasiveness of four different human renal cell carcinoma (RCC) cell lines of the clear cell type was investigated. Different PKC-inhibitors markedly inhibited invasiveness of the highly invasive cell lines, suggesting an invasion-promoting role of PKC in human RCC. Analysis of PKC-isoenzyme expression by protein fractionation and immunoblotting revealed that all cell lines expressed PKC-α, -ɛ, -ζ, -μ and -ι as known from normal kidney tissue. Interestingly, PKC-δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 25 publications
4
32
1
1
Order By: Relevance
“…Various isoforms of PKC have been implicated in ovarian tumorigenesis and drug resistance [56][57][58][59][60][61][62]. Involvement of PKCε in tumor development, invasion, and metastasis have been shown in other tissues [50,[63][64][65][66][67]. However, little is known about the roles of PKCε in ovarian cancer and, in light of the results reported here, this PKC isoform certainly deserves further consideration in ovarian tumorigenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Various isoforms of PKC have been implicated in ovarian tumorigenesis and drug resistance [56][57][58][59][60][61][62]. Involvement of PKCε in tumor development, invasion, and metastasis have been shown in other tissues [50,[63][64][65][66][67]. However, little is known about the roles of PKCε in ovarian cancer and, in light of the results reported here, this PKC isoform certainly deserves further consideration in ovarian tumorigenesis.…”
Section: Discussionmentioning
confidence: 90%
“…We have found that pro-apoptotic activity of α-TOS positively correlated with its inhibitory activity on protein kinase C (PKC) (Neuzil et al, 2001), and PKC activity has been associated with a more proliferative and invasive phenotype of malignant cells, as shown e.g. for breast (Ways et al, 1995) or renal carcinoma cells (Engers et al, 2000). Moreover, PKC is also involved in fast transition through the cell cycle by regulating the cell cycle checkpoint proteins p…”
Section: Short Communicationmentioning
confidence: 97%
“…PKCε and -α membrane localization, which reflects the activation status of the enzymes, was associated with the invasiveness of human renal cell carcinomas (RCCs) [54]. NIH 3T3 fibroblasts overexpressing PKCε were invasive and displayed polarized morphology with extended long cellular membrane protrusions [55].…”
Section: Pkcε a Unique Pkc With Oncogenic Potentialmentioning
confidence: 99%